Antimicrobial Activity of Aristolochia bracteata - Elizabeth, K.M.; Suryanarayana Raju, Ch. (Asian Journal of Chemistry, 2010)
Antimicrobial activity of Aristolochia bracteata was tested against several human pathogenic microorganisms by disc diffusion method. The methanol extract of fruits gave rise to three substances, namely, cold methanol extract, distilled methanol extract and residual methanol extract. Crude aqueous extract was also tried. The crude extract at a concentration of 4 mg/disc showed zones of inhibition ranging from 11–27 mm. This showed highest zone of inhibition against S. aureus, i.e., 27 mm. The distilled methanol extract exhibited a range of 12–17 mm zones, cold extract 14–22.5 mm and the residual extract 15–22.5 mm. Methanol control showed zones ranging from 10–16 mm. The minimal inhibitory concentration of residual extract against these pathogens was determined which ranged from 50–800 μg/mL. The amylase and protease production was assessed in few strains and it was found that there was 78.2% reduction in the amylase activity of Y. enterocolitica and 100 and 60% reduction in amylase and protease production of P. aeruginosa following the treatment with residual extract of this fruit extract. From these observations it can be attributed that A. bracteata possesses strong antimicrobial activity.